The external environment driving internal organizational change: empirical evidence from commercial banks’ adoption of Islamic financial transactions in Libya - Gader Khalleefah Bin Idrees, Salwa Abdel; Syed Jaafar Alhabshi, Syed Musa; Ashurov, Sharofiddin; Abdullah Othman, Anwar Hasan (IIUM Institute of Islamic Banking and Finance (IIiBF), 2021)
This paper examines the Libyan commercial banks’ adoption of Islamic financial transactions to achieve a real value for stakeholders related to internal environmental adaptation. Accordingly, a questionnaire was designed and distributed to 14 commercial banks in Libya. Structural Equation Modelling (SEM) has been employed for testing the hypotheses. In the context of hypothesized modeling, the conceptual framework portrayed the constructs of the variables employed in the study to be Libyan commercial banks’ adoption of financial transactions as the dependent variable and the external environment as factors driving organizational change as the independent variable. The adaptation of the commercial banks’ internal environment acts as a mediating variable. The Confirmatory Factor Analysis (CFA) is applied to the relationship between measures of constructs and indicators. The results showed that the estimations of maximum likelihood (ML) were satisfactory. The results of SEM showed that commercial banks’ adoption of Islamic financial transactions is more related to their capability of adapting their internal environment than achieving an economic and social value of stakeholders. Finally, the article provides future research directions on commercial banks’ ability to adapt to their internal environment to drive change and commercial banks’ adoption of Islamic financial transactions.